Multiple Similarity Solutions Of Steady And Unsteady Convection Boundary Layer Flows In Viscous Fluids And Nanofluids - Mohd Rohni, Azizah (2013)
For many complex problems in convection boundary layer flow and heat transfer, multiple solutions may exist due to the nonlinearity of the differential equations, variation of geometric or fluid mechanical parameters. It is difficult to visualize the occurrence of multiple solutions experimentally, therefore mathematical computation is important to provide the details flow structure and to notice the occurrence of multiple solutions. This thesis aims to study the possible multiple similarity solutions that might exist in boundary layer flows and heat transfer. This is done by considering five different problems which are two problems in viscous fluid, one problem in nanofluid and the remaining two are in porous medium and in porous medium filled with nanofluid, respectively. For the problems in viscous fluid and nanofluid, different situations of shrinking sheet have been considered. On the other hand, vertical plate in porous medium and vertical cylinder in porous medium filled by nanofluid have also been considered. The basic governing equations in partial differential equations form for each problem are first transformed into similarity equations in nonlinear ordinary differential equations form by similarity approach. The resulting systems are then solved numerically using the shooting technique with the aid of shootlib fuction in Maple software. This technique involves Runge-Kutta method together with Newton-Raphson correction.